Three-dimensional computed tomography mapping techniques in the morphometric analysis of AO/OTA 33A and 33C distal femoral fractures: a retrospective single-center study - Chen, Song; Zheng, Zhenxin; Guo, Jinku; Hong, Shengkun; Zhou, Weijun; Xie, Jun; Wang, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: Complex distal femoral fractures involve a challenging set of considerations that must be known to provide optimal management. This study aimed to determine the location and frequency of fracture lines and comminution zones in AO/OTA types 33A and 33C distal femoral fractures using three-dimensional computed tomography mapping. Methods: Seventy-four consecutive eligible patients were included. Fracture fragments for each patient were reconstructed, virtually reduced, and adjusted to match the distal femoral template. Then, all fracture lines and comminuted areas were extracted in transparent mode, and corresponding heat maps were constructed. Finally, these maps, along with the quantitative analysis findings of the counts and volumes of each fragment, were used to summarize the characteristics of the fractures. Results: Thirty-four females and 40 males (average age, 58 years [range, 18 to 92years]) presented with a distal femoral fracture. There were 53 AO/OTA type 33A fractures, and 21 AO/OTA type 33C fractures. These two patterns differed significantly on fracture fragment count, comminuted zone fracture fragment count, and mean comminuted zone fracture fragment volume (P < 0.05). Most of the fracture line heat zones were in the femoral epiphysis, intercondylar notch of the femur, and patellofemoral joint. The comminuted area heat regions were mostly found on the lateral, anterior, and posterior femoral diaphysis, with less involvement on the medial side. Conclusion: Our findings may serve as a guide for the surgical approach selection of complex distal femur fractures, the placement strategy of the internal fixation, and the optimization of the osteotomy plan for biomechanical studies.